Cyber security Threat Mitigation in Architectures for Industrial IOT - Mishra, Triveni; SaikatGochhait (International Journal of Psychosocial Rehabilitation, 2020)
The industrial IOT applications are rapidly growing and transforming the traditional industries to smart industries (Industry 4.0), along with the impending consumer IOT adoption. It is therefore necessary to adapt and deploy a reliable cyber security software architecture. Due to the immense security challenges in IIOT, this paper tries to approach the concerns from an end-to-end IIOT solution security perspective. In this paper, we discuss the current architectural framework and study how they can address challenges like scalability, integration problems, data privacy, and security, and how the framework improves the security in the IIOT environment and reduces cost. With respect to the aspect of cost, we highlight the factors and specific costs in developing an IOT application. This paper also explains the security requirements, practices, and types of attacks on the IOT architecture. Here, we highlight the critical problems (threats/attacks/vulnerabilities) and their detection, prevention, and mitigation techniques. The authors aim is to prepare a study of existing protocols, frameworks, and architectures currently proposed in active research based on various parameters as well as to review the existing technology and project requirements in IIOT to understand both technology and stakeholder impact over IIOT security.